The dynamics of the Potts-Bethe mapping over ℚ_p: the case p ≡ 2 (mod 3) - Saburov, Mansoor; Ahmad, Mohd Ali Khameini (IOP Publishing, 2017)
In this paper, we study the dynamics of the Potts-Bethe mapping associated with the p-adic q-state Potts model over the Cayley tree of order three. Namely, we establish the regularity of the Potts-Bethe mapping for the case p = 2 (mod 3) with p > 5.